Level of Utilization of Main and Functional Facilities Coastal Fishing Port Tobelo North Halmahera District - Tou, Mujais; Karman, Amirul; Kaidati, Bahar (Agrikan: Jurnal Agribisnis Perikanan, 2021)
The success of development the coastal fishing port in Tobelo of North Halmahera Regency cannot be separated from the existence of basic, functional and supporting facilities, therefore it is necessary to know the conditions and level of utilization of these facilities. The objectives of the research are; describe the existing condition of main and functional facilities and analyze the level of utilization of the main and functional facilities at the Tobelo coastal fishing port, North Halmahera Regency. The research was conducted at the Tobelo coastal fishing port, North Halmahera Regency, for one month, namely in November 2020. The research method used was a case study. The condition of the existence of basic facilities at PPP Tobelo, namely the length of the pier having a capacity of 80.00 m, an area of the port pool of 100 m2, the depth of the pier waters -5.00. The existing condition of functional facilities is an ice factory consisting of 2 units (each with a capacity of 5 tonnes a day), ABF consisting of 2 units (each with a capacity of 5 tonnes / 24 hours) and cold storage consisting of 2 units (each with a capacity of 50 tonnes). The utilization rate of the length of the pier and port pond exceeds the optimal limit of the installed capacity, then the utilization rate of the depth of the pier waters, ice factory, air blast freezer, and cold storage is not optimal.